Blend & paint using 3D render paint-over techniques for art ([Amsterdam, the Netherlands] Blender Foundation, 2011)
On this DVD training - with over 2 hours of videos - David Revoy explains step-by-step his 3D paint-over techniques. The training starts with an instroduction to Blender 2.5, to provide 2D artists with not much 3D experience a quick overview of the key features of Blender. It introduces the basics of the UI, modeling meshes and setting up light and rendering. This render is then taken to MyPaint and GIMP for further processing, importing and setting up several layers and showing how to efficiently add detail, texture and more dramatic lightning with manual paint-overs and layering techniques.
The main theme of this training is to end up with a big high-detail 6K picture of a science-fiction environment, with space ship, a city, plants and trees, and several characters. By using the example files on the DVD one cal fully recreate this artwork, but the real goal of the training is to understand the workflow, to train techniques to make efficient changes in visual appearances, learning to redo steps continuously.
DVD
For this training, a basic knowledge of Gimp and digital painting is recommended. It is an ideal DVD for 2D artist to spice up their workflow with a bit of 3D, and for 3D artist to stimulate them to paint more often, as an efficient design tool. Over 2 hours of videos of 1280x720, 30fps. Short, concise steps, commented with english labels (no voice-over). Uses Blender 2.5+-Gimp-painter 2.6+ - Mypaint 0.9+. Licensed as Creative Commons 3 Attribution.
Contents:1. Blender Quickstart. This section is for beginners, especially targeted at 2D artists, who want to learn the essential 3D tools to produce a 3D render for a paint-over. a) Blender UI; b) Blender Basics; c) Blender Modeling part 1; d) Blender Modeling part 2; e) Blender Light/Camera/Render.--2. Making the Illustration "The mission". The main section shows all steps for 3D modeling and painting a highly detailed environment with a city, trees, spaceship and people. This section is still work in progress, and the author might take side-steps with other illustrations to demonstrate techniques. a)Mission - Modeling the spaceship; b)Mission - Modeling the background; c) Mission - Light and rendering; d) Mission - Texturing; e) Mission - Render and layers; f) Mission - Import in Gimp; g) Mission - Gimp part a; h) Mission - Gimp part b; i) Mission - Gimp part c; j) Mission - Gimp part d; k) Mission - Mypaint part a; l) Mission - Mypaint part b; m) Mission - Mypaint part c; n) Mission - Mypaint part d.
Bonus and extra documentation on the DVD.
Keywords: Computer drawing; Computer drawing -- Study and teaching; Computer graphics